Pengembangan LKPD Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis pada Materi Ikatan Kimia Fase F SMA/MA - Khairanisa, Ayudia; Fitri, Bali Yana; Hardeli, Hardeli (MASALIQ, 2025)
Chemistry lessons not only focus on mastering basic concepts, but also on developing critical thinking skills. The development of critical thinking skills in chemistry lessons has not been supported by good conditions in the field. This can be seen from the use of conventional learning models and teaching materials that are often used, namely only package books. So that to fulfill the effective learning process, teaching materials are needed that can help students achieve critical thinking skills. This research aims to produce a PBL-based LKPD to improve critical thinking skills in chemical bonding material phase F SMA/MA. This type of research is Educational Design Research with the Plomp development model. The subjects of this study are UNP chemistry lecturers, chemistry teachers of SMAN 1 Koto XI Tarusan and students of SMAN 1 Koto XI Tarusan. Data was obtained from validity questionnaires, practicality sheets, and pretest and posttest scores. The validation data was processed using Aiken's V formula. Based on the results found, it can be concluded that the LKPD developed is already in the valid category with an Aiken's V value of 0.88 and is very practical with a percentage of practicality based on teacher assessments of 92% and students of 91%. To see the improvement of critical thinking skills, pretest and posttest were carried out for students. Based on the results of the study, an N-Gain value of 0.7 was obtained. It can be concluded that LKPD is valid and very practical to be used in learning and is efficiently used to improve students' critical thinking skills.